The role of emerging countries in global food security - Fan, Shenggen; Brzeska, Joanna (International Food Policy Research Institute, 2010)
Global food insecurity remains a serious problem. In 2010, more than 900 million people are still hungry, and progress toward reaching the first Millennium Development Goal of halving the world's proportion of malnourished people is off track by a wide margin. But the global environment within which food insecurity persists is changing in important ways. Emerging countries such as Brazil, China, and India, which have experienced rapid growth and increased integration with the global economy in recent years, have significant potential to contribute to global food security-not only by alleviating hunger among their own citizens, but also by increasing trade and financial linkages as well as technology and knowledge exchanges with developing countries.